The Bippolo Seed and other lost stories - Seuss, Dr.; Cohen, Charles D. (New York : Random House, 2011)
Presents seven Dr. Seuss stories first published in magazines between 1948 and 1959, with an introduction and commentary on each.
The Bippolo Seed -- The rabbit, the bear, and the Zinniga- Zanniga -- Gustav the Goldfish -- Tadd and Todd -- Steak for supper -- The strange shirt spot -- The great Henry McBride.
Keywords: Children's stories, American; Stories in rhyme; Short stories